Türkiye Cumhuriyeti’nin Musevi politikaları (1930-1950) - Ahmed, Ferida Haboubı Ep (My University, 2018)
Giriş ve altı bölüm oluşan bu çalışmanın kronolojik çerçevesi Hazar Devleti’nden 1950’ye kadar bir dönem kapsamaktadır. Bilindiği üzere 1492 yılında İspanya’dan sürülen Yahudiler Osmanlı devletine sığınmış oldukları gibi yine 1930’lu yıllardan İkinci Dünya Savaşı sonuna kadar Avrupa Yahudileri baskıdan kaçarak Türkiye’ye yerleştiler. Avrupa’da artan antisemitizm 1934 yılında Türkiye’de yaşanmamakta, Türkiye yönetimi Yahudilere karşı olumlu bir tutum izlemekteydi. Söz konusu İkinci Dünya Savaşı sırasında Fransa’nın bir kısmı Nazi Almanya’sı tarafından işgal edilmiştir. Türkiye, Fransa’da yaşayan Türk Musevileri veya Türk kökenli Musevileri kurtarmada önemli bir rol oynamıştır. Türk Musevileri kurtarmak için Fransa’daki görev yapan Türk diplomatlar Ankara hükümetinin bağlantıları ve talimatları ile müdahale etmişlerdir.

The chronological framework of this thesis which consists of an introduction and six chapters covers the period from the Caspian State to 1950. Thousands of Sepharadic Jews had been expelled from Spain in 1492 taken refuge in the Ottoman State where the exiles were welcomed. Again from the 1930’s until the end of the Second World War, many European Jews who had fled from Nazi persecution succeded in escaping to Turkey. The rise of anti-Semitism in Europe was reflected in Turkey. The Thrace incidents of 1934 are considered to be examples of descrimination. However, Turkey’s government adopted a positive attitude towards the Jews. During the Second World War a part of France was occupied by Nazi Germany, as a result the Turkish government played an important role to save Turkish Jews or Turkish descent Jews who were living in German-occupied France and were also subjected to Nazi persecution. In this context, the Turkish Diplomats in France spent a good deal to rescue them from being killed, all along with instructions from Ankara government which took various measures and legal regulations to repatriate their Jewish citizens.
Keywords: Büyükelçilik; Citizenship; Filistin; France; Fransa; History; Hitler; Immigration; İkinci Dünya Savaşı; Jews; Minorities; Musevi; Nazi; Palestine; Second World War; Tarih; Turkey; Türkiye; Vichy; Yahudi